The algebra of wealth ebook A simple formula for financial security. - Galloway, Scott (2024)
AN INSTANT #1 NEW YORK TIMES BESTSELLER A must-have guide to optimizing your life for wealth and success, from bestselling author, NYU professor, and cohost of the Pivot podcast Scott Galloway. Today’s workers have more opportunities and mobility than any generation before. They also face unprecedented challenges, including inflation, labor and housing shortages, and climate volatility. Even the notion of retirement is undergoing a profound rethink, as our lifespans extend and our relationship with work evolves. In this environment, the tried-and-true financial advice our parents followed is no longer enough. It’s time for a new playbook. In The Algebra of Wealth , Scott Galloway lays bare the rules of financial success in today’s economy. In his characteristic unvarnished, no-BS style, he explains what you need to know in order to better your chances for economic security no matter what. You’ll learn: How to find and follow your talent, not your passion, when making career decisions How to ride and optimize big economic waves (hard truth: market dynamics always trump individual achievement) What small steps you can take that pay big returns later, including diversification and tax planning How stoicism can help you minimize spending and develop better financial habits Brimming with wise, game-changing advice from one of the world’s most popular business school professors, The Algebra of Wealth offers a powerful framework for making the most of what opportunities come your way.